SWOT Analysis and ANP for Organic Tempeh SME Business Development Strategy - Manik Ayu Titisari; Denis Fidita Karya; Surjo Hadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: Therefore, in this study, SWOT analysis is used to formulate problems from internal and external factors, from developing alternative strategies, selecting and making strategic decisions that align with company goals.